Smart Greenhouse Monitoring and Control System for Temperature and Humidity - Mohd Anuar Zamani, Mohamad Haziq; Jumaat, Siti Amely (Evolution in Electrical and Electronic Engineering, 2023)
The " Smart Greenhouse Monitoring and Control System for Temperature and Humidity" is a useful and effective method for keeping track of and controlling temperature and humidity in greenhouses. It continuously monitors and regulates the temperature and humidity levels to make sure the greenhouse’s environment is perfect for crop development. The system uses sensors for real-time data collection and microcontrollers for precise control. For accuracy, responsiveness, energy efficiency, and all-around stability, it has been rigorously tested and assessed. The outcomes show how well the system works to keep the greenhouse at its best environmental conditions. In greenhouse farming, using this cutting-edge monitoring and control technology has various advantages. It guards against heat stress and encourages ideal growing conditions, increasing crop production. Additionally, it optimizes resource usage by using real-time data for automated and focused operations. By presenting an efficient and long-lasting solution, this initiative advances greenhouse farming methods. In conclusion, the "Greenhouse Smart Monitoring and Control System for Temperature and Humidity" project provides a small, clever system that optimizes greenhouse temperature and humidity levels. Through automated control mechanisms, it maintains the best growth conditions, increases crop output, and supports sustainable farming practices.